DNA replication studies with coliphage 186: the involvement of the Escherichia coli DnaA protein in 186 replication is indirect. - Williams, S G (1994)
The inability of coliphage 186 to infect productively a dnaA(Ts) mutant at a restrictive temperature was confirmed. However, the requirement by 186 for DnaA is indirect, since 186 can successfully infect suppressed dnaA (null) strains. The block to 186 infection of a dnaA(Ts) strain at a restrictive temperature is at the level of replication but incompletely so, since some 20% of the phage specific replication seen with infection of a dnaA+ host does occur. A mutant screen, to isolate host mutants blocked in 186-specific replication but not in the replication of the close relative coliphage P2, which has no DnaA requirement, yielded a mutant whose locus we mapped to the rep gene. A 186 mutant able to infect this rep mutant was isolated, and the mutation was located in the phage replication initiation endonuclease gene A, suggesting direct interaction between the Rep helicase and phage endonuclease during replication. DNA sequencing indicated a glutamic acid-to-valine change at residue 155 of the 694-residue product of gene A. In the discussion, we speculate that the indirect need of DnaA function is at the level of lagging-strand synthesis in the rolling circle replication of 186.